Felt Stigma and Its Underlying Contributors in Epilepsy Patients - Mao, Lingyan; Wang, Keying; Zhang, Qianqian; Wang, Jing; Zhao, Yanan; Peng, Weifeng; Ding, Jing (Frontiers in Public Health, 2022)
Objective To explore the correlated clinical and psychological factors of stigmatization and investigate the relationship between stigma and white matter abnormalities in epilepsy patients. Methods Stigmatization was obtained by a three-item stigma scale in 256 epilepsy patients with genetic or unknown etiology. Personality and quality of life (QOL) were assessed by Eysenck Personality Questionnaire (EPQ) and QOL-31 questionnaire respectively. One hundred and fourteen of them were performed Hamilton Depression Scale-17 (HAMD) and scanned with diffusion tensor imaging in 3T MRI. Fractional anisotropy (FA) values of frontotemporal contact fibers were calculated. Results There were about 39.8% patients felt stigma, with the highest score (Score 3) in 8.2% (21/256). Stigma scores were significantly negatively correlated with education (P < 0.01), age of onset (P < 0.05), extraversion score of EPQ (P < 0.01), total and all the subscale QOL scores (P < 0.001), and positively correlated with duration (P < 0.01), HAMD score (P < 0.001), neuroticism score of EPQ (P < 0.001). We found negative correlation between stigma scores and FA values of right superior longitudinal fasciculus and left cingulum (P < 0.05). Logistic regression results showed that FA value of left cingulum (P = 0.011; OR = 0.000), social function (P = 0.000; OR = 0.935) of QOL, and neuroticism score of EPQ (P = 0.033; OR = 1.123) independently correlated to felt stigma. Conclusion Felt stigma in epilepsy patients was found to be correlated with neuroticism, depression, and deficient social function of QOL, which might be predisposed by the impairment of the left cingulum. Our results provide preliminary evidence for the underlying neural circuits in stigmatization.